Chemical composition of cell walls in velamentous roots of epiphytic Orchidaceae - Joca, Thais Arruda Costa [UNESP]; Oliveira, Denis Coelho de; Zotz, Gerhard; Cardoso, Joao Custodio Fernandes; Moreira, Ana Silvia Franco Pinheiro (Springer, 2020)
The chemical composition of the cell walls strongly affects water permeability and storage in root tissues. Since epiphytic orchids live in a habitat with a highly fluctuating water supply, the root cell walls are functionally important. In the present study, we used histochemistry and immunocytochemistry techniques in order to determine the composition of the cell walls of root tissues of 18 epiphytic species belonging to seven subtribes across the Orchidaceae. The impregnation of lignin in the velamen cells reinforces its function as mechanical support and can facilitate apoplastic flow. Pectins, as well cellulose and lignins, are also essential for the stability and mechanical support of velamen cells. The exodermis and endodermis possess a suberinized lamella and often lignified walls that function as selective barriers to apoplastic flow. Various cortical parenchyma secondary wall thickenings, including phi, reticulated, and uniform, prevent the cortex from collapsing during periods of desiccation. The presence of highly methyl-esterified pectins in the cortical parenchyma facilitates the formation of gels, causing wall loosening and increased porosity, which contributes to water storage and solute transport between cells. Finally, cells with lipid or lignin impregnation in the cortical parenchyma could increase the water flow towards the stele.
Keywords: Aerial roots; Epiphytic orchids; Lignin; Pectins; Velamen; Water absorption